2018
DOI: 10.1155/2018/4319604
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and Ethnocultural Factors Limit the Physical Activity of Rural Sri Lankan Patients with Diabetes Mellitus

Abstract: South Asians have high prevalence of diabetes, cardiovascular risk, and physical inactivity. Reasons for physical inactivity have not been explored among Asians living within their endogenous environments. During phase 1 of the study, we assessed the physical activity (PA) of the population using a quantitative, descriptive, cross-sectional research method. During phase 2 of the study, a qualitative method with in-depth interviews was used to collect data on barriers of PA. Four hundred patients with type 2 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The findings of this study showed that persons with T2D-HF with more than 2 chronic conditions were more likely to adhere to an exercise regimen. 69 As Beverily et al 70 reported, the presence of more comorbid conditions may have motivated our study participants to be more attentive to exercise as a strategy to reduce T2D and HF progression and the associated adverse events. In addition, clinicians in urban academic health science settings may be more likely to recommend and encourage exercise to improve health outcomes than those in rural or disadvantaged settings.…”
Section: Discussionmentioning
confidence: 94%
“…The findings of this study showed that persons with T2D-HF with more than 2 chronic conditions were more likely to adhere to an exercise regimen. 69 As Beverily et al 70 reported, the presence of more comorbid conditions may have motivated our study participants to be more attentive to exercise as a strategy to reduce T2D and HF progression and the associated adverse events. In addition, clinicians in urban academic health science settings may be more likely to recommend and encourage exercise to improve health outcomes than those in rural or disadvantaged settings.…”
Section: Discussionmentioning
confidence: 94%
“…However, Fern andez-Mart ınez et al (2020) confirm the reverse, arguing that women are more physically active, and their tendency of exercising in fitness centers is relatively higher in developed countries. Further, adverse health status is found to be negatively associated with exercising due to risk of injury, less self-efficacy and social support (Medagama and Galgomuwa, 2018;Karunanayake et al, 2020). The similar trend is uncovered with regard to individuals with health insurance policies (Birdee et al, 2013).…”
Section: Introductionmentioning
confidence: 65%
“…Also, a majority of literature is based on national-level household surveys of developed-countries. The results might be different in less developed countries where the conditions required to enhance social capital are more limited (Bornstein et al, 2012), and extensive databases are not frequently available (Medagama and Galgomuwa, 2018). In Sri Lankan context, Medagama and Galgomuwa (2018) and Karunanayake et al (2020)…”
Section: Introductionmentioning
confidence: 98%
“…There are several reasons as to why people do not engage in regular physical activity. Lack of time management, unavailability and unaffordability of facilities for physical exercises, several myths related to physical activity are perceived to be few main reasons (12).…”
Section: Sustaining Physical Activity Practicesmentioning
confidence: 99%